Penentuan rasio optimum campuran CPO: batubara dalam desulfurisasi dan deashing secara flotasi sistem kontinyu - Andi Aladin (Jurnal Rekayasa Proses, 2009)
The problem related to the utilisation of Indonesian coal is the high sulphur and ash contents of the coal which may defect the combustor units and pollute the environment. Flotation is one of the methods to reduce the inorganic sulphur and ash in coal. Research on desulphurisation and deashing of coal from Mallawa (Sulawesi) was performed in a continuous flotation column. Variables which give maximum desulphurisation were studied and covered in this article, e.g. mixing ratio of crude palm oil (CPO) surfactant to coal. It was found that optimum mixing ratio of CPO to coal was 1:4, based on optimum conditions previously determined, i.e. resident time of 60 minutes, air flow rate of 1.22 l/min, pH 6.5 and coal particle size of 169 m. In these optimum conditions, the sulphur content was reduced from 3.3% to 0.93% or 72% sulphur recovery, while the ash content was reduced from 11.25% to 9.75%, the calorific value was maintained at 6000 kcal/kg. The desulphurised and deashed coal meets the specification criteria of the industrial fuel.